(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The establishment of a micro-propagation protocol for banana (Musa sp.) cv. Sabri, was carried out using meristematic stem cuttings explant. MS medium supplemented with BAP singly or in combination with auxin, IAA and coconut water was used for this purpose. Highest percentage of shoot regeneration (90%) and maximum number of shoots (10) per explant were observed when cultured on MS + 4.0 mg/1 BAP + 2.0 mg/1 IAA + 13% (v/v) coconut water. Best response towards root induction was achieved on half MS medium supplemented with 0.5 mg/1 IBA. The regenerated healthy rooted plantlets were transferred to small plastic pot containing garden soil and compost in a ratio of 2:1. Through this method, complete micro-propagated plantlets were obtained within three months. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11444 Bangladesh J. Sci. Ind. Res. 47(2), 143-146, 2012